Slides to Philosophy 167: Class 14 -- Newton's De Motu Corporum, Version 3 -- Part 11. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Generally corresponds to the video segment: Class 14, Part 11.